2017
DOI: 10.17116/jnevro20171172242-49
|View full text |Cite
|
Sign up to set email alerts
|

The influence of solar and geomagnetic activity on the risk of multiple sclerosis (results of correlation and regression analysis)

Abstract: CA revealed the association between the MS onset and mean values of kp-index in the onset year and the year before the onset year, number of days with kp≥4 and kp≥5 in the onset year and the year before the onset year, mean SFU in the onset year. RA revealed the association between the MS onset and mean kp in the year before the onset year and in the onset year, number of days with kp≥7 in the onset year and the year before the onset year, mean kp during pregnancy, number of days with kp≥7 in the 1st year of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…They also found that exposure to GMD during the first decade of life has a cumulative effect on the risk of obtaining MS in adulthood. A similar result has been observed recently by Samoylova et al in Russia [ 32 ].…”
Section: Supporting Evidencessupporting
confidence: 92%
“…They also found that exposure to GMD during the first decade of life has a cumulative effect on the risk of obtaining MS in adulthood. A similar result has been observed recently by Samoylova et al in Russia [ 32 ].…”
Section: Supporting Evidencessupporting
confidence: 92%